Fibroblast Growth Factor 21 Attenuates Diabetes-Induced Renal Fibrosis by Negatively Regulating TGF-β-p53-Smad2/3-Mediated Epithelial-to-Mesenchymal Transition via Activation of AKT - Sundong Lin; Lechu Yu; Yongqing Ni; Lulu He; Xiaolu Weng; Xuemian Lu; Chi Zhang (Diabetes & Metabolism Journal, 2020)
BackgroundEpithelial-to-mesenchymal transition (EMT) is required for renal fibrosis, which is a characteristic of diabetic nephropathy (DN). Our previous study demonstrated that fibroblast growth factor 21 (FGF21) prevented DN associated with the suppressing renal connective tissue growth factor expression, a key marker of renal fibrosis. Therefore, the effects of FGF21 on renal fibrosis in a DN mouse model and the underlying mechanisms were investigated in this study.MethodsType 1 diabetes mellitus was induced in C57BL/6J mice by intraperitoneal injections of multiple low doses of streptozotocin. Then, diabetic and non-diabetic mice were treated with or without FGF21 in the presence of pifithrin-α (p53 inhibitor) or 10-[4′-(N,N-Diethylamino)butyl]-2-chlorophenoxazine hydrochloride (10-DEBC) hydrochloride (Akt inhibitor) for 4 months.ResultsDN was diagnosed by renal dysfunction, hypertrophy, tubulointerstitial lesions, and glomerulosclerosis associated with severe fibrosis, all of which were prevented by FGF21. FGF21 also suppressed the diabetes-induced renal EMT in DN mice by negatively regulating transforming growth factor beta (TGF-β)-induced nuclear translocation of Smad2/3, which is required for the transcription of multiple fibrotic genes. The mechanistic studies showed that FGF21 attenuated nuclear translocation of Smad2/3 by inhibiting renal activity of its conjugated protein p53, which carries Smad2/3 into the nucleus. Moreover pifithrin-α inhibited the FGF21-induced preventive effects on the renal EMT and subsequent renal fibrosis in DN mice. In addition, 10-DEBC also blocked FGF21-induced inhibition of renal p53 activity by phosphorylation of mouse double minute-2 homolog (MDM2).ConclusionFGF21 prevents renal fibrosis via negative regulation of the TGF-β/Smad2/3-mediated EMT process by activation of the Akt/MDM2/p53 signaling pathway.